2020
DOI: 10.3389/fpsyg.2020.610876
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Validating Tests of Reading and Listening Comprehension for Fifth and Sixth Grade Students in Portugal

Abstract: An efficient assessment of reading and linguistic abilities in school children requires reliable and valid measures. Moreover, measures which include specific test forms for different academic grade levels, that are vertically equated, allow the direct comparison of results across multiple time points and avoid floor and ceiling effects. Two studies were conducted to achieve these goals. The purpose of the first study was to develop tests of reading and listening comprehension in European Portuguese, with vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…Reading, on the other hand, is less dependent on grade-specific knowledge, and reading has also shown as a skill measurable across multiple grades in both English and other languages (e.g. Australian Curriculum, Assessment and Reporting Authority, 2014;Beaton & Johnson, 1992;Diakidoy, Stylianou, Karefillidou, & Papageorgiou, 2005;Rodrigues et al, 2020). Within the Norwegian context, it is natural to assume the other national tests measuring reading in Norwegian and reading in English could be vertically scaled post-hoc.…”
Section: Possible Implications In the Norwegian Contextmentioning
confidence: 99%
“…Reading, on the other hand, is less dependent on grade-specific knowledge, and reading has also shown as a skill measurable across multiple grades in both English and other languages (e.g. Australian Curriculum, Assessment and Reporting Authority, 2014;Beaton & Johnson, 1992;Diakidoy, Stylianou, Karefillidou, & Papageorgiou, 2005;Rodrigues et al, 2020). Within the Norwegian context, it is natural to assume the other national tests measuring reading in Norwegian and reading in English could be vertically scaled post-hoc.…”
Section: Possible Implications In the Norwegian Contextmentioning
confidence: 99%
“…It is composed of five vertically scaled forms that assesses reading comprehension of narrative texts in students from second to sixth grades (Rodrigues et al, 2020;Santos et al, 2016). Students were instructed to read silently a set of texts and answer a set of multiple-choice questions (three options) about them.…”
Section: Test Of Reading Comprehension Of Narrative Texts [Tctml-n Te...mentioning
confidence: 99%
“…We performed a nonsystematic review in PubMed and Science Direct (using the terms, "reading comprehension" and "equating" or "concurrent calibration") and we found only 32 studies. From these, only nine were related to equating reading comprehension tasks with real data (Ree et al, 2003;Betts et al, 2009;von Davier, 2013;Liao et al, 2014;Dimitrov, 2016;Sandefur, 2018;Seo et al, 2018;Wagner et al, 2018;Rodrigues et al, 2020). In general, these studies present a wide diversity of approaches for reporting equating.…”
Section: Introductionmentioning
confidence: 99%
“…A great part of the research in the educational area used classic or observed scores approaches to equating (Ree et al, 2003;Betts et al, 2009;von Davier, 2013;Wagner et al, 2018). Most part of the studies that used IRT approach used Rasch models, which do not provide information about the discrimination of the items (Liao et al, 2014;Sandefur, 2018;Seo et al, 2018;Rodrigues et al, 2020). The exception is the study of Dimitrov (2016) that used 3PLM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation